Three-Dimensional Cell Counting based on Two Dimensional Cross-Section Images - Anton, J.; Saar, T. (Elektronika ir Elektrotechnika, 2011)
This paper presents an automated method for effective quantitative measurement of cells in different Arabidopsis root tips. The plant reaction to the nitric oxide needs to be measured, therefore the root cell proliferation has to be calculated. Cross section images of these root tips are the input of the application implemented. It consists of a two parts methods which are presented here: 1) A combination of several image processing algorithms is proposed in order to overcome images defects (burry, overlapping) and correctly detect the cell distribution. 2) Using the information from the processed images, a three-dimensional tracking process over all frames is accomplished in order to calculate the total number of cells in each root tip. Practical simulations and experimental results are presented to show the performance and efficiency of this method for cell tracking. Ill. 6, bibl. 5 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.455